Bank Mergers and the Free-Rider Problem in the Philippine Banking Industry - Manuela, Wilfred, Jr. S. (Philippine Management Review; Vol 11 (2004), 2016)
This study investigates the excess returns around the merger dates using data on Philippine banks involved in mergers and acquisitions for the period 1999-2002.  The methodology makes use of a unit root test for the daily and cumulative abnormal returns to test the free-rider problem hypothesis.  A unit root test verifies whether a shock, in this case a merger or acquisition, to the excess return or Ait is permanent or temporary.  The free-rider problem occurs when the impact of a shock to Ait is permanent, while it does not occur when the impact is temporary.  Using the constant and linear trend as exogenous variables in the time series equation, the results indicate that the impact of a shock on daily excess returns is temporary, while its impact on the cumulative excess returns is permanent.  The non-rejection of the null hypothesis in the unit root tests performed on cumulative excess returns seems to indicate that the free-rider problem can occur and that investors with information tend to profit from cumulative excess returns.